Corrosion-resistant and biofouling-resistant multi-principal-element alloys and their preparation methods and applications

By preparing Cr, Ni, Cu, V, Fe multi-main alloys, and using laser powder bed melting technology, the problems of easy corrosion and fouling and processing of offshore equipment are solved, and complex structure forming with high strength, corrosion resistance and fouling resistance are achieved, which is suitable for marine engineering equipment.

CN120193195BActive Publication Date: 2025-08-12BEIJING UNIV OF TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510669125.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-05-23
Publication Date
2025-08-12
Estimated Expiration
2045-05-23

AI Technical Summary

Technical Problem

Metal components of marine engineering equipment are easily corroded, easily biofouled, and difficult to flexibly process complex structures. The existing anti-fouling coatings pose environmental threats, and traditional processing technology has great limitations.

Method used

Multi-main alloys, including Cr, Ni, Cu, V, and Fe elements, are used to prepare disordered FCC solid solution and supersaturated Cu-rich solid solution structures through laser powder bed melting technology. Combined with reasonable process parameters, the release of Cu elements and the distribution of V elements are controlled to form antibacterial and anti-fouling effects.

Benefits of technology

It realizes a multi-main alloy with high strength, corrosion resistance and biofouling resistance, and can form complex structural components in one step, has excellent mechanical properties and environmentally friendly anti-fouling effect, reducing energy consumption and maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120193195B_ABST
    Figure CN120193195B_ABST
Patent Text Reader

Abstract

The present invention provides a corrosion-resistant, biofouling-resistant multi-principal alloy, its preparation method, and application. The multi-principal alloy comprises the following components by mass percentage: 17-22% Cr, 17-25% Ni, 10-15% Cu, 0.3-0.5% V, and the balance Fe. The multi-principal alloy is obtained by processing the above metal materials into a multi-principal-component pre-alloyed powder and then preparing it using laser powder bed melting technology. The pre-alloyed powder is primarily composed of a disordered FCC solid solution and a supersaturated Cu-rich solid solution structure. The multi-principal-component alloy provided by the present invention has excellent mechanical strength and corrosion resistance, while also being able to inhibit the attachment of marine organisms. Combined with the above preparation method, it can be used to form various complex structural components in one step, and has important applications in the field of marine engineering equipment manufacturing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of alloy materials, and in particular to a corrosion-resistant and biofouling-resistant multi-principal-element alloy and a preparation method and application thereof. Background Art

[0002] The harsh, complex, and ever-changing marine environment, characterized by high salinity in the atmosphere and seawater, and a diverse array of marine species, has led to increasingly prominent corrosion and fouling issues for offshore equipment and coastal facilities. Marine biofouling increases ship drag, reduces speed, and increases energy consumption, severely limiting fuel efficiency. Furthermore, corrosion on metal surfaces significantly impacts the performance and service life of offshore equipment, increasing maintenance costs. Furthermore, marine biofouling can lead to invasive species and reduce aquaculture production. Consequently, corrosion and marine biofouling have become a major challenge hindering the development of marine resources and marine engineering in my country.

[0003] Improving the corrosion resistance of metal components in offshore equipment has attracted widespread attention, including the development of new alloy materials and the preparation of corrosion-resistant surface coatings. Typical examples include 316 stainless steel and nickel-based alloys. However, marine organisms are susceptible to attaching to these materials, causing fouling. Currently, copper alloys are the most widely used anti-fouling materials, primarily utilizing copper ions released by copper corrosion to inhibit the attachment of fouling organisms. However, copper alloys suffer from significant corrosion resistance limitations, and corrosion products easily accumulate on their surfaces, compromising their anti-fouling capabilities and further limiting their application. Common anti-fouling measures include mechanical removal, electrochemical removal, ultrasonic removal, and the application of anti-fouling coatings. Anti-fouling coatings are the most economical and effective means of preventing marine fouling organisms from attaching to equipment surfaces. The anti-fouling effect of marine anti-fouling coatings is primarily due to the continuous release of toxic materials from the coatings into the environment, killing marine organisms. However, these toxic materials pose a serious threat to the marine environment and can easily cause marine ecological problems. Therefore, there is an urgent engineering need to develop more effective and environmentally friendly marine corrosion-resistant and anti-biofouling materials.

[0004] Furthermore, most metal structural components in marine engineering equipment are manufactured using traditional manufacturing processes, such as casting, forging, and welding, and require complex post-processing, such as multiple deformation and heat treatment, to improve mechanical properties. However, with the continuous development of marine development, the demand for a variety of high-performance and complex structural components is increasing, and traditional processing techniques have shown certain limitations. Furthermore, to ensure precision and high mechanical properties, the surfaces of such complex structural components are not suitable for the preparation of corrosion-resistant and anti-fouling coatings. Therefore, the development of a metal structural material with inherent corrosion resistance and resistance to marine fouling, and its preparation method, is of great significance to the marine industry. Summary of the Invention

[0005] The present invention provides a corrosion-resistant, biofouling-resistant multi-principal-element alloy and its preparation method and application, which are used to solve the bottleneck problem in the prior art that metal parts of marine engineering equipment are easily corroded, easily biofouled, and difficult to flexibly process complex structures, and realize the preparation of high-strength, corrosion-resistant, biofouling-resistant multi-principal-element alloys and related complex structural parts of marine engineering equipment.

[0006] In a first aspect, the present invention provides a multi-principal alloy comprising the following components: 15-25% Cr, 15-25% Ni, 10-20% Cu, 0.1%-0.7% V, and the balance Fe;

[0007] The above-mentioned multi-principal alloy is prepared by laser powder bed melting technology and is mainly composed of disordered FCC solid solution and supersaturated Cu-rich solid solution structure.

[0008] Preferably, the multi-principal-element alloy comprises the following components: 17-22% Cr, 17-25% Ni, 10-15% Cu, 0.3-0.5% V and the balance Fe.

[0009] Further preferably, the multi-principal-element alloy comprises the following components: 21% Cr, 20% Ni, 15% Cu, 0.4% V and the balance Fe.

[0010] Among the above components, the three transition metal elements Cr, Fe, and Ni have similar atomic radii, allowing for good mutual solubility. This facilitates the formation of a single-phase solid solution structure, ensuring good material processability and promoting the quality of laser powder bed fusion forming. Nearly equal molar ratios of Cr, Fe, and Ni promote the formation of a disordered FCC phase, and sufficient Cr ensures the alloy's corrosion resistance. The introduction of a large amount of Ni into the alloy not only maintains the overall FCC phase structure of the alloy, but also allows for the solid dissolution of more Cu to facilitate the forming process, preventing the precipitation of a large amount of Cu-rich phase (ε-Cu) that can trigger galvanic corrosion.

[0011] The purpose of introducing Cu is to release Cu ions, which can interact with microbial cell membranes, disrupting their integrity and inhibiting microbial attachment, thereby achieving bactericidal and anti-biofouling effects. However, the Cu content must be strictly controlled because its solid solubility in Fe-based alloys is very limited (generally less than 5wt.%). Introducing excessive Cu can easily precipitate a brittle ε-Cu phase, significantly deteriorating the alloy's mechanical properties and corrosion resistance.

[0012] The present invention also adds a certain amount of V. On the one hand, V can refine the grain size and strengthen the grain boundaries by pinning, thereby improving the overall mechanical properties of the alloy. On the other hand, V is an extremely strong carbide and nitride former, purifying trace impurities in the molten alloy and preventing the consumption of the corrosion-resistant element Cr in the matrix. Furthermore, V has a certain degree of biotoxicity. The layer-by-layer deposition characteristics of additive manufacturing, combined with reasonable process control, can induce V and Cu to form a small amount of metastable Cu-V interphase between dendrites, thereby promoting the precipitation of Cu ions between the grains and synergistically enhancing the antibacterial and antifouling effects. However, the V content requires careful design. Excessive V can lead to the formation of coarse intermetallic compounds (such as Ni-V) in the alloy, increase the alloy's brittleness, exacerbate localized corrosion, and undermine the alloy's overall corrosion resistance.

[0013] Preferably, the disordered FCC solid solution is located within the dendrites;

[0014] and / or the supersaturated Cu-rich solid solution is located between dendrites;

[0015] The corrosion current density of the above multi-element alloy in artificial seawater is 57.0~70.6 nA / cm 2 , pitting potential is 0.614~0.898V SCE The antibacterial rate of Pseudomonas aeruginosa within 48 hours was 98.1%~99.9%, the anti-algae attachment rate within 72 hours was 98.3%~99.0%, the yield strength was 525~602MPa, the tensile strength was 631~697MPa, and the elongation was 20.4~30.8%.

[0016] The multi-principal alloy maintains the FCC solid solution structure as a whole, which can effectively guarantee the quality of the alloy laser powder bed melting forming, while avoiding the severe galvanic corrosion easily caused by the heterogeneous phase structure. However, the effective control of the intragranular and intergranular structure is the key to ensuring the improvement of the overall mechanical properties, corrosion resistance and anti-fouling properties of the alloy. Among them, maintaining the disordered FCC structure of the main body of the intragranular structure can improve the comprehensive mechanical properties of the alloy, especially the plastic deformation ability and machinability, and help to form complex structural components and avoid cracks or stress deformation; while the supersaturated Cu-rich solid solution (Cu-FCC) formed between the dendrites can ensure the corrosion resistance and mechanical properties of the alloy while using the grain boundaries or subgrain boundaries to provide energy and channels for the release and diffusion of Cu ions, thereby improving the resistance to microbial corrosion and anti-marine fouling.

[0017] In a second aspect, the present invention provides a method for preparing the above-mentioned multi-principal component alloy, comprising:

[0018] (1) Cr, Ni, Cu, V, and Fe bulk materials were prepared into multi-principal element pre-alloyed powders by inert gas atomization method;

[0019] (2) The multi-principal component pre-alloyed powder is prepared into a multi-principal component alloy using laser powder bed melting technology.

[0020] Preferably, the purity of the Cr, Ni, Cu, V, and Fe bulk materials in step (1) of the above-mentioned preparation method is greater than 99wt.%;

[0021] The particle size of the prepared multi-principal component pre-alloyed powder is 25-53 μm.

[0022] Preferably, the parameters of the laser powder bed melting technology in step (2) of the above-mentioned preparation method are: laser power 80~120W, scanning speed 1100~1500mm / s, scanning spacing 0.04~0.06mm, layer thickness 0.02mm, scanning strategy is checkerboard, interlayer rotation is 67°, and protective gas is argon.

[0023] The multi-principal alloy provided by the present invention exhibits excellent corrosion and anti-fouling properties primarily due to the rational combination of component design and preparation methods. The Cu element used in the present invention typically has a negative impact on the alloy's mechanical properties and corrosion resistance. In particular, Cu has very limited solid solubility in Fe-based alloys, and the resulting Cu-rich precipitates (ε-Cu) significantly reduce the alloy's cold working deformability and induce galvanic corrosion. To address this issue, the present invention utilizes the unique characteristics of laser powder bed fusion technology and manipulates process parameters. First, the melt pool is controlled to reduce the melt pool aspect ratio while increasing the melt pool cooling rate, promoting lateral diffusion of Cu within the melt pool and thereby increasing its solubility within the alloy. Second, the solidification microstructure is shaped by process parameters to control the formation location of the supersaturated Cu-rich solid solution (FCC), directing its formation primarily between dendrites. This not only inhibits the formation of brittle intermetallic compounds within the grains and reduces the consumption of corrosion-resistant elements, but also expands the FCC austenite phase, promoting the efficient release of Cu ions. This ensures both mechanical and corrosion resistance while enhancing the alloy's anti-fouling properties. In addition, the reasonable combination of composition and process can also induce the trace V element in the alloy to segregate between dendrites and react with the Cu-rich FCC solid solution to form a small amount of dispersed metastable Cu-V intermediate phase, thereby promoting the precipitation of intergranular Cu ions and synergistically improving the antibacterial and anti-fouling effects.

[0024] In a third aspect, the present invention provides the use of the above-mentioned multi-principal-element alloy or the above-mentioned preparation method in the preparation of complex structural components of corrosion-resistant and anti-biofouling equipment.

[0025] In summary, the present invention obtains a multi-principal-element alloy with excellent corrosion resistance and anti-fouling properties by rationally selecting and controlling the proportions of Cr, Ni, Cu, V, and Fe elements, combined with the laser powder bed melting process and supporting process parameters.

[0026] Preferably, the complex structural components of the corrosion-resistant and anti-biofouling equipment in the above-mentioned applications are complex structural components in marine engineering equipment, such as marine environment monitoring sensor housings, underwater robot brackets, seawater treatment valves, and key connection nodes of marine platforms.

[0027] The multi-principal-element alloy and preparation method thereof provided by the present invention can form complex structural components in one step without any post-processing process, with high forming precision, and is particularly suitable for the processing and manufacturing of complex structural components in marine engineering equipment.

[0028] In a fourth aspect, the present invention provides a complex structural component of marine engineering equipment, which contains the above-mentioned multi-principal element alloy or the multi-principal element alloy produced by the above-mentioned method.

[0029] The present invention has the following beneficial effects:

[0030] (1) The multi-element alloy prepared by the laser powder bed fusion technology of the present invention has a yield strength exceeding 525MPa, a tensile strength exceeding 631MPa, an elongation exceeding 20%, and a self-corrosion current density of less than 70.6nA / cm in artificial seawater. 2 , pitting potential is higher than 0.6V SCE .

[0031] (2) The multi-principal element alloy prepared by the laser powder bed melting technology of the present invention has an antibacterial rate of more than 98.1% against typical marine bacteria within 48 hours, inhibits the reproduction and attachment behavior of typical marine algae organisms, and has an anti-algae attachment rate of more than 98.3%.

[0032] (3) The multi-principal-element alloy and its preparation method provided by the present invention can form complex structural components in one step without any post-processing process and with high forming precision.

[0033] (4) The multi-principal element alloy prepared by laser powder bed melting provided by the present invention has high mechanical properties, corrosion resistance and resistance to marine biofouling, and can be used as a structural component material in marine engineering equipment. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the technical solutions in the present invention or the prior art, a brief introduction will be given below to the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0035] Figure 1 This is the potentiodynamic polarization curve of Example 2 in an artificial seawater solution environment.

[0036] Figure 2This is the room temperature tensile curve of Example 2.

[0037] Figure 3 The antibacterial plate test results of Example 2 and Comparative Example 5 are shown in FIG. Figure 3 (a) is the result of Example 2, Figure 3 (b) is the result of Comparative Example 5. DETAILED DESCRIPTION

[0038] To make the objectives, technical solutions, and advantages of the present invention more clear, the technical solutions of the present invention will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the embodiments described are only some of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts shall fall within the scope of protection of the present invention.

[0039] In the present invention, all instruments used without manufacturer indication are conventional products that can be purchased through regular channels. The methods described are conventional methods unless otherwise specified, and the raw materials described are commercially available unless otherwise specified.

[0040] In the following embodiments:

[0041] The raw materials used were bulk nickel, iron, chromium, copper, and vanadium with a purity greater than 99% by weight. Pre-alloyed powders with a particle size range of 25-53 μm were prepared using inert gas atomization. A 316 stainless steel substrate was used, and the surface was pre-cleaned and decontaminated. The alloy was formed using an EOS M100 laser powder bed fusion (LPBF) system, using a checkerboard scanning strategy, 67° inter-layer rotation, and argon as the shielding gas.

[0042] Example 1

[0043] The alloy chemical composition and percentage by mass in this example are: 17% Cr, 17% Ni, 13% Cu, and 0.1% V. The balance is Fe and other unavoidable impurities. The laser powder bed fusion additive manufacturing process parameters are: laser power 80 W, scan pitch 0.04 mm, scan speed 1100 mm / s, and powder layer thickness 0.02 mm.

[0044] Example 2

[0045] The alloy chemical composition and percentage by mass in this embodiment are: Cr 21%, Ni 20%, Cu 15%, V 0.4%, with the balance being Fe and other unavoidable impurities. The laser powder bed fusion additive manufacturing process parameters are: laser power 100 W, scan pitch 0.04 mm, scan speed 1400 mm / s, and powder layer thickness 0.02 mm.

[0046] Example 3

[0047] The alloy chemical composition and percentage by mass in this embodiment are: Cr 18%, Ni 22%, Cu 15%, V 0.4%, with the balance being Fe and other unavoidable impurities. The laser powder bed fusion additive manufacturing process parameters are: laser power 90W, scan pitch 0.04mm, scan speed 1300mm / s, and powder layer thickness 0.02mm.

[0048] Example 4

[0049] The alloy chemical composition and percentage by mass in this embodiment are: 20% Cr, 20% Ni, 11% Cu, and 0.2% V, with the balance being Fe and other unavoidable impurities. The laser powder bed fusion additive manufacturing process parameters are: laser power of 100 W, scan pitch of 0.05 mm, scan speed of 1200 mm / s, and powder layer thickness of 0.01 mm.

[0050] Example 5

[0051] The alloy chemical composition and percentage by mass in this embodiment are: Cr 21%, Ni 22%, Cu 12%, V 0.2%, with the balance being Fe and other unavoidable impurities. The laser powder bed fusion additive manufacturing process parameters are: laser power 100 W, scan pitch 0.05 mm, scan speed 1200 mm / s, and powder layer thickness 0.03 mm.

[0052] Example 6

[0053] The alloy chemical composition and percentage by mass in this embodiment are: 20% Cr, 23% Ni, 14% Cu, and 0.3% V. The balance is Fe and other unavoidable impurities. The laser powder bed fusion additive manufacturing process parameters are: laser power of 110 W, scan pitch of 0.05 mm, scan speed of 1400 mm / s, and powder layer thickness of 0.02 mm.

[0054] Example 7

[0055] The alloy chemical composition and percentage by mass in this embodiment are: 22% Cr, 25% Ni, 10% Cu, and 0.1% V. The balance is Fe and other unavoidable impurities. The laser powder bed fusion additive manufacturing process parameters are: laser power of 120 W, scan pitch of 0.06 mm, scan speed of 1200 mm / s, and powder layer thickness of 0.02 mm.

[0056] Example 8

[0057] The alloy chemical composition and percentage by mass in this embodiment are: Cr 21%, Ni 18%, Cu 13%, V 0.4%, with the balance being Fe and other unavoidable impurities. The laser powder bed fusion additive manufacturing process parameters are: laser power 100 W, scan pitch 0.04 mm, scan speed 1400 mm / s, and powder layer thickness 0.02 mm.

[0058] Comparative Example 1

[0059] The alloy composition and percentage by mass in this comparative example are: 22% Cr, 25% Ni, 22% Cu, with the balance being Fe and other unavoidable impurities. The laser powder bed fusion additive manufacturing process parameters are: laser power of 100 W, scan pitch of 0.05 mm, scan speed of 1200 mm / s, and powder layer thickness of 0.02 mm.

[0060] Comparative Example 2

[0061] The alloy chemical composition and percentage by mass in this comparative example are: 20% Cr, 21% Ni, 5% Cu, and 1% V. The balance is Fe and other unavoidable impurities. The laser powder bed fusion additive manufacturing process parameters are: laser power 80W, scan pitch 0.04mm, scan speed 1100mm / s, and powder layer thickness 0.02mm.

[0062] Comparative Example 3

[0063] The alloy chemical composition and percentage by mass in this comparative example are: 20% Cr, 21% Ni, 8% Cu, 0.1% V, with the balance being Fe and other unavoidable impurities. The laser powder bed fusion additive manufacturing process parameters are: laser power 70W, scan pitch 0.04mm, scan speed 800mm / s, and powder layer thickness 0.02mm.

[0064] Comparative Example 4

[0065] The alloy chemical composition and percentage by mass in this comparative example are: 17% Cr, 17% Ni, 13% Cu, and 0.2% V. The balance is Fe and other unavoidable impurities. The laser powder bed fusion additive manufacturing process parameters are: laser power of 100 W, scan pitch of 0.07 mm, scan speed of 1000 mm / s, and powder layer thickness of 0.02 mm.

[0066] Comparative Example 5

[0067] The alloy powder in this comparative example is 316L stainless steel. The laser powder bed fusion additive manufacturing process parameters are: laser power of 100 W, scanning pitch of 0.04 mm, scanning speed of 1400 mm / s, and powder layer thickness of 0.02 mm.

[0068] The following methods were used to test the properties of the multi-principal alloys prepared in each embodiment and comparative example:

[0069] (1) Quasi-static tensile mechanical property test: A CMT4305 microcomputer electronic universal testing machine was used to conduct the room temperature quasi-static tensile test. The I-shaped specimens were made according to the relevant provisions of the national standard for room temperature tensile test of metal materials (GB / T228.1-2010). The specimens were 1.0 mm thick, 3.14 mm wide, 10 mm long for the parallel section, 5 mm long for the gauge length, and the strain rate was 1×10 -3 s -1 .

[0070] (2) Antibacterial performance test: According to relevant standards such as "JIS Z 2801-2000 "Antibacterial processed products - Antibacterial test method and antibacterial effect", GB / T 2591-2003 "Antibacterial performance test method and antibacterial effect of antibacterial plastics", the antibacterial rate of the laser additively manufactured multi-principal alloy shown in the embodiment after being acted on typical bacteria in the marine environment (Pseudomonas aeruginosa) was quantitatively tested. The incubation time was set to 48 hours, and the co-cultured bacterial concentration was set to (1-2)×10 5 CFU / mL. The antibacterial performance test results are shown in Table 1, where the antibacterial rate is calculated as follows: Antibacterial rate (%) = [(number of viable bacteria on the surface of the control alloy sample - number of viable bacteria on the surface of the multi-principal alloy) / number of viable bacteria on the surface of the control alloy sample] × 100%. The control alloy is a conventional cast 316L stainless steel block material.

[0071] (3) Characterization of marine biological attachment: The attachment experiment was conducted using a typical marine algae, Navicula, which was cultured in a constant temperature shaking incubator at 22°C, with a cycle of 12 hours of day and 12 hours of night. When the Navicula was in the exponential growth phase, it was taken out and used for the attachment experiment. 1 mL of the solution was used with a concentration of (5-6) × 10 6 mL -1 Samples were submerged in a seawater suspension of Navicula and incubated in a 22°C constant-temperature shaking incubator for 72 hours, following a 12-hour day / 12-hour night cycle. After removal, the samples were rinsed with sterile artificial seawater to remove any unattached Navicula. The samples were then fixed with 2.5% glutaraldehyde prepared in artificial seawater at 4°C for 4 hours and observed using a scanning electron microscope. The area of Navicula attachment was counted using the image method.

[0072] (4) Corrosion resistance testing: Using an electrochemical workstation, the potentiodynamic polarization curve of the alloy in artificial seawater solution was tested to obtain the corrosion current density and pitting potential, thereby quantitatively evaluating the corrosion resistance of the multi-principal element alloy.

[0073] The results of the above performance tests are shown in Table 1. The potentiodynamic polarization curve of the multi-principal element alloy prepared in Example 2 in an artificial seawater solution environment is shown in Table 1. Figure 1 As shown, the room temperature tensile curve of the multi-principal alloy prepared in Example 2 is as follows Figure 2 As shown in the figure, the antibacterial plate test results of the multi-principal alloy prepared in Example 2 and Comparative Example 5 are as follows: Figure 3 shown.

[0074]

[0075] As shown in Table 1, each embodiment of the present invention obtains an FCC structure multi-principal element alloy composed of a disordered FCC solid solution and a supersaturated Cu-rich solid solution structure, and has mechanical properties of a yield strength exceeding 525 MPa, a tensile strength exceeding 631 MPa, and an elongation exceeding 20%, and a self-corrosion current density in artificial seawater lower than 70.6 nA / cm 2 , pitting potential is higher than 0.6V SCE The antibacterial rate of Pseudomonas aeruginosa exceeded 98.1% in 48 hours, and the anti-algae adhesion rate exceeded 98.3% in 72 hours, and the best effect was obtained in Example 2.

[0076] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the various embodiments of the present invention.

Claims

1. A multi-principal alloy, characterized in that: The alloy comprises the following components: 15-25 wt% of Cr, 15-25 wt% of Ni, 10-20 wt% of Cu, 0.1 wt%-0.7 wt% of V and the balance of Fe; The multi-principal alloy is prepared by laser powder bed melting technology, and its microstructure consists of a disordered FCC solid solution and a supersaturated Cu-rich solid solution structure; The disordered FCC solid solution is located in the dendrite; The supersaturated Cu-rich solid solution is located between dendrites.

2. The multi-principal-component alloy according to claim 1, characterized in that: The alloy comprises the following components: 17-22 wt% Cr, 17-25 wt% Ni, 10-15 wt% Cu, 0.3 wt%-0.5 wt% V and the balance Fe.

3. The multi-principal-component alloy according to claim 2, characterized in that: The alloy comprises the following components: 21 wt% Cr, 20 wt% Ni, 15 wt% Cu, 0.4 wt% V and the balance Fe.

4. The multi-principal-component alloy according to claim 3, characterized in that: The self-corrosion current density of the multi-principal alloy in artificial seawater is 57.0-70.6 nA / cm 2 , pitting potential is 0.614~0.898V SCE The antibacterial rate of Pseudomonas aeruginosa within 48 hours was 98.1%~99.9%, the anti-algae attachment rate within 72 hours was 98.3%~99.0%, the yield strength was 525~602MPa, the tensile strength was 631~697MPa, and the elongation was 20.4~30.8%.

5. The method for preparing the multi-principal component alloy according to any one of claims 1 to 4, characterized in that: include: (1) Cr, Ni, Cu, V, and Fe bulk materials were prepared into multi-principal element pre-alloyed powders by inert gas atomization method; (2) The multi-principal component pre-alloyed powder is prepared into a multi-principal component alloy using laser powder bed melting technology.

6. The preparation method according to claim 5, characterized in that The purity of the Cr, Ni, Cu, V, and Fe bulk materials in step (1) is greater than 99wt.%; The particle size of the prepared multi-principal component pre-alloyed powder is 25-53 μm.

7. The preparation method according to claim 5, characterized in that The parameters of the laser powder bed melting technology in step (2) are: laser power 80~120W, scanning speed 1100~1500mm / s, scanning spacing 0.04~0.06mm, layer thickness 0.02mm, scanning strategy is checkerboard, interlayer rotation is 67°, and protective gas is argon.

8. Use of the multi-principal-element alloy according to any one of claims 1 to 4 or the preparation method according to any one of claims 5 to 7 in the preparation of complex structural components of corrosion-resistant and biofouling-resistant equipment.

9. The use according to claim 8, characterized in that The complex structural components of the corrosion-resistant and biofouling-resistant equipment are key components in marine engineering equipment.

10. A complex structural component of marine engineering equipment, characterized in that: A multi-principal-component alloy comprising the multi-principal-component alloy according to any one of claims 1 to 4 or a multi-principal-component alloy prepared by the method according to any one of claims 5 to 7.

Citation Information

Patent Citations

  • Antibacterial and antiviral copper-containing stainless steel and preparation and application thereof

    CN114000066A

  • Laser additive manufacturing method for improving mechanical property of FCC structure multi-principal element alloy

    CN117444234A